Introduction: Orality and Technauriture of African Literatures - (:unkn) unknown (My University, 2014)
African oral cultures as well as their oral literatures are vigorous. True, in some cases, elements of such literatures are at risk of disappearing when styles and texts are linked to specific languages and rituals that are no longer performed as they were in the past; in other cases, the very limited number of speakers has drawn local and global attention to endangered languages and the need for their revitalization.1 Still, such a “sense of an ending” needs to be balanced by the observation that the large majority of the verbal arts and the cultural groups that produce them have, by and large, integrated oral and new ways of expression—from hip hop to various forms of theatre, world fusion music and digital orality. Changing oral genres and “technauriture” in African literatures are at the heart of the analyses and discussions presented in this number of Tydskrif vir Letterkunde.
Keywords: African Research